Aging and episodic memory specificity: Evidence challenging a domain-general pattern separation decline - Ariana Youm; Melanie Cohn; Katherine Duncan (PLoS ONE, 2025)
Aging is associated with a decline in episodic memory specificity. This phenomenon has been observed across various memory tasks, such as the Mnemonic Similarity Task (MST), where older adults show a heightened tendency to falsely recognize perceptually similar items. While many studies suggest this impairment reflects a generalized reduction in pattern separation, others indicate that older adults may exhibit preserved discrimination abilities for semantic representations. Furthermore, pattern separation accounts also posit that a bias toward pattern completion, a process whereby partial cues reactivate whole representations, occurs with aging. However, the evidence for this shift remains mixed, which may be in part due to how pattern completion is commonly measured. The current study aimed to investigate whether aging affects memory discrimination for semantically similar content, using tasks that minimize reliance on visual-spatial processing and executive functioning, both of which tend to decline with age. We designed two independent tasks that respectively tax memory specificity and pattern completion: the Verbal Discrimination Task (VDT) and the Verbal Completion Task (VCT). Sixty-six younger adults and 66 older adults completed these tasks, and a subset also completed the Object MST (younger n = 33 and older n = 35) to allow for a direct comparison between visual and semantic similarity. Our results showed that, compared to younger adults, older adults exhibited greater deficits in memory specificity for perceptually similar lures (Object MST) than for semantically similar content (VDT), suggesting that age-related memory impairments may be more pronounced in perceptual domains. Additionally, older adults showed reduced performance on the VCT, suggesting that deficits in memory specificity may be independent of deficits in pattern completion. Together, these findings go against the view that age-related differences in memory specificity are strictly rooted in a modality-general pattern separation deficit.